As formas do mando: conformismo e decadência em Graciliano Ramos - Silva, Adriana Furtuoso da (2021)
This work deals with the forms of command in two books by Graciliano Ramos: Vidas Secas and São Bernardo. Here in this study, the command is seen as a synonym for authority, direct command, dominance, order, power, sovereignty. In the first work, we have the abstract and anonymous command, represented by unnamed characters that represent a social structure in which Fabiano perceives himself dominated. This command becomes operational from the perspective of the oppressed and its apparent conformity - the retiree is subjugated by his situation of misery accentuated by drought; he is animalized by his condition of exclusion with destitution of goods and speech; he is exploited and deceived by the boss, as well as humiliated due to the abuse of authority of the yellow soldier, representative of an absent State. In the second work, in the oppressor's view, we have a command personified by a figure without scruples - the ambitious Paulo Honório, who exercises dominion over everything and everyone around him, including his wife Madalena. As that dominance and authority diminishes, the character is taken to a stage of decay. The theoretical framework of this analysis comprises the contributions of Antonio Candido, João Luiz Lafetá, Lourival Holanda, Ana Paula Pacheco, Sônia Brayner, Hermenegildo Bastos, Alfredo Bosi, Luís Bueno, among others, whose ideas are explained and discussed throughout the chapters. Known for his skillful writing, which integrates social criticism and singular aesthetics, Graciliano's text allows us an analysis supported by what Candido called structural reduction, as a kind of internalization of the elements external to the work. Thus, the social factors related to the two works in question appear in the form of literary choices made by the author. In this way, the first two chapters of the dissertation present an overview of each novel, showing how their structure is interwoven with the elements of Mandonism, the same that oppresses Fabiano and makes Paulo Honório a dominator. The final chapter takes up points of tension and intersection with regard to the language used in the two works, establishing a parallel between them and highlighting elements such as dryness, silence, and memory. The discourse and attitudes of the oppressed and the oppressor are resumed, always in a concomitant perspective of social criticism and narrative construction.